Pendekatan Jawabir dan Zawajir: Teori Behavioral Prevention terhadap Perspektif Ibrahim Hosen dalam Praktik Pencegahan Riba - Patih, Husnama; Rufaedah, Dina Anisya (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The Jawabir and Zawajir approach in the context of Islamic criminal law offers two different perspectives on law enforcement and crime prevention. Jawabir, which means coercion, focuses on the application of punishment as outlined in the textual provisions of the Qur'an and Hadith, aimed at atoning for the sins of criminals. On the other hand, Zawajir, which means prevention, emphasizes the importance of preventing crimes before they occur to create a deterrent effect for the wider community. Ibrahim Hosen, a prominent figure in ushul fiqh in Indonesia, proposed a reinterpretation of these two approaches. He emphasized that the application of law should be more flexible and responsive to the times and the needs of society. Hosen argues that the Zawajir approach is more relevant in the modern context, as it functions not only as punishment but also as a means of rehabilitation and prevention. Through the application of behavioral prevention theory, Hosen emphasizes that punishment should not only be retributive but also preventive, aiming to reduce the likelihood of future crime recurrence. As such, this approach seeks to strike a balance between justice and the public good. This study uses a qualitative library research method with content analysis, comparing classical Islamic legal texts and modern criminological theories. The findings indicate that Zawajir aligns closely with behavioral prevention, offering a preventive and reformative model compatible with maqasid al-sharia. This research contributes by bridging Islamic legal traditions and modern behavioral approaches to strengthen preventive strategies against riba.